KATA-KATA MAKIAN DALAM FILM A GOOD DAY TO DIE HARD OLEH SKIP WOODS - MAHAMURAH, RANNY CLAUDIA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT Â This research is entitled â€œSwear Words in the Movie A Good Day to Die Hard by Skip Woodsâ€. In language, swear word is an important phenomenon to be analyzed because it can provide a deeper understanding about the unique of swear words and how they can communicate the emotion of the speaker to the listener. The objectives of this research are to identify and classify the categories of swear words and to analyze and describe the functions of swear words. This research uses a descriptive method. There are three steps to finish this research. First step is preparation, the writer watched the movie to find out the data. Second step is data collection, the writer read the printed script to get more accurate data and identified all the swear words then the writer listed them. Third step is data analysis, the writer used two theories, i.e.the theory ofMcEnery (2006:27) to identify and classify the categories of swear wordsand the theory of Anderssonand Hirsch (1985:53-56)to analyze and describe the functions of swear words. The results of this research show that there are 72 swear words found in A Good Day to Die Hard movie. According to the theory of McEnery (2006:27),Â there are fifteen categories of swear words, but there were only seven categories of swear words found in this movie, those are Cursing Expletive, Emphatic Adverb, Figurative Extension, General Expletive, Idiomatic, â€˜Pronominalâ€™ Form, and Personal Insult. Furthermore, the functions of using swear words in this movie are Expletive, Abusive, Humoristic, Euphemistic, and Habitual. The findings of this research support the theory of McEnery and the theory of Andersson and Hirsch. Â Keywords : Swear Words; A Good Day to Die Hard; McEnery, Andersson and Hirsch Â